Perilaku Disiplin Bangun Pagi saat Pembelajaran di Masa Covid 19 Kelompok B di TK Fransiskus - Kefi, Maria Marsela; Sulistianah, Sulistianah (UNIVED Press, Universitas Dehasen Bengkulu, 2022)
This study aims to describe the disciplined behavior of getting up early in the COVID-19 period in early childhood. Discipline has recently been felt as something of concern, one of which is the discipline of getting up early, especially in early childhood. During the COVID-19 pandemic, early childhood also experienced distance learning. Understanding distance learning, it is assumed by early childhood that studying at home means they are off. This affects the habit of getting up in the morning. Therefore, the moral aspect that needs to be built in schools is how children get used to a disciplined life. The method used in this research is qualitative method. The results of the study were obtained from 6 respondents who had a lack of discipline in getting up in the morning, starting to be disciplined in getting up early, and being disciplined in getting up early. The conclusion from the results of the study found that the discipline of getting up early during the Covid 19 period in Tulip class B group children at Fransiskus Pringsewu Kindergarten showed good development, with efforts from parents, teachers and the environment to improve disciplined behavior in getting up early from an early age, so that participants learn to develop optimally.